Modelagem condicional específica da gestão de risco de mercado nos BRIC - Cruz, Francisco Rogério Gomes (2013)
Although the bloc labeled BRIC is composed of emerging economies characterized by heterogeneity in economic, social and political aspects, there are empirical evidences about the convergence and partial financial integration. In this sense, we address the risk management of most relevant BRIC market indices through Value at Risk approach, based on a parametric Gaussian and unconditional version, and also extending it intending to accommodate violations of heteroscedasticity and non-normality of daily returns. Corroborating previous and specific evidences, as Jianshe (2007) for the Chinese market, Karmakar (2005) for the Indian and Thupayagale (2010) for Russian, we are able to show that it is necessary to adapt the canonical framework, because of the statistical idiosyncrasies of time series, using the critical values related to the best fitting probability distribution, and modeling the evolution of the conditional risk. We also provide a dynamic measure of risk-return performance of theses indices from the perspective of local investors.